2019
DOI: 10.1021/jacs.9b10620
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion Forces Drive the Formation of Uranium–Alkane Adducts

Abstract: Single-crystal cryogenic X-ray diffraction at 6 K, electron paramagnetic resonance spectroscopy, and correlated electronic structure calculations are combined to shed light on the nature of the metal−tris(aryloxide) and η 2 −H, C metal−alkane interactions in the [(( t•Bu ArO) 3 tacn)U III ( Me cy-C6)]•( Me cy-C6) adduct. An analysis of the ligand field experienced by the uranium center using ab initio ligand field theory in combination with the angular overlap model yields rather unusual U−O ArO and U−N tacn b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 36 publications
3
16
1
Order By: Relevance
“…These solution-based techniques provide unequivocal evidence for alkane coordination at a metal center. However, their use for the subsequent isolation of a crystalline material that allows for detailed structural characterization using single-crystal X-ray diffraction, or onward reactivity studies, has yet to be realized. , This is because rapid alkane displacement by a solvent or a photogenerated ligand leads to lifetimes unsuitable for solution-based crystallization techniques, a situation compounded by the low temperatures used and less than 100% photoconversations achieved.…”
Section: Introductionmentioning
confidence: 99%
“…These solution-based techniques provide unequivocal evidence for alkane coordination at a metal center. However, their use for the subsequent isolation of a crystalline material that allows for detailed structural characterization using single-crystal X-ray diffraction, or onward reactivity studies, has yet to be realized. , This is because rapid alkane displacement by a solvent or a photogenerated ligand leads to lifetimes unsuitable for solution-based crystallization techniques, a situation compounded by the low temperatures used and less than 100% photoconversations achieved.…”
Section: Introductionmentioning
confidence: 99%
“…The coordination chemistry of f-block metals supported by tripodal ligands has attracted considerable attention and resulted in new coordination modes and selective small molecule activation. Most notably, Meyer and co-workers developed an arene-anchored tris­(aryloxide) tripodal ligand system and showed that it can stabilize multiple oxidation states of f-block elements, including lanthanides and uranium, as well as empowering redox catalysis. , In particular, the arene anchor of Meyer’s ligand played an important role in tuning the electronic structures at the metal centers. , Inspired by this work, we aimed to develop a tripodal tris­(amido) ligand system with an arene anchor to combine the strong donating ability of amido ligands and the ambiphilic nature of the arene anchor. Despite the ubiquity of amido ligands in coordination chemistry, to the best of our knowledge, no example of tripodal-type tris­(amido) ligands with an arene anchor has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…99 Finally, crystallographic evidence for η 2 -C,H coordination of an alkane to the uranium(III) tris(aryloxide) complex (( tBu,tBu ArO)3tacn)U (( R,R′ ArOH)3tacn = 1,4,7-tris((2-hydroxy-3-R-5-R′-phenyl)methyl)-1,4,7-triazacyclononane) was reported in 2003; 100 a more recent study attributed alkane binding to London dispersion interactions with the (( tBu,tBu ArO)3tacn) 3− ligand. 101…”
Section: Redox-neutral Adduct Formationmentioning
confidence: 99%